HUBUNGAN ANTARA FAKTOR PERSONAL (GENDER, SOSIO EKONOMI, RAS) DENGAN INTEGRITAS AKADEMIK MAHASISWA PROGRAM STUDI PENDIDIKAN DOKTER 2014 - Jamaluddin Ahmad Ali Mas'ud (FKU 15 UMY 572, 2015)
ix ABSTRACT Background: Integrity is one of the cultural duties and functions with full responsibility, honest and virtuous and uphold the ethics of the profession. There are five main values are included in the academic integrity are honesty, trust, fairness, respect and responsibility. As health professionals such as doctors expected to have values of academic integrity in their profession later, so it should start from when university education is when a student medical education courses. The purpose of this study was conducted to determine whether there is a relationship between personal factors (gender, socio-economic, race) with the academic integrity of the student of medical education. Methods: The study design was cross-sectional descriptive analytic involving 77 students of medical education to be a respondent. The questionnaire used is a questionnaire from Roff (2009) which has been modified and has been tested for validity and reliability. Questionnaires sided 30 statements about the behavior of academic integrity violations / academic cheating and every statement is followed by five questions that describe the perception and behavior of students. Data analysis was performed using Chi-Square test as to find the relationship between nominal scale variables with ordinal scale variables. Results: The results of this study showed that the relationship between gender with the academic integrity of the student of medical education p value> 0.05, then the relationship between socio-economic with the academic integrity of the student of medical education p value> 0.05, and the relationship between race with the academic integrity of the student of medical education p value> 0.05. P values> 0.05 gives the result that there is no correlation between the two variables. Conclusion: There is no relationship between personal factors (gender, socioeconomic, race) with the academic integrity of the student of medical education. Keywords: Personal factors, gender, economic sisio, race, academic integrity, academic fraud, breach of academic integrity, a medical student. x INTISARI Latar Belakang: Integritas merupakan salah satu budaya yang menjalankan tugas dan fungsi dengan penuh tanggung jawab, jujur dan berbudi luhur serta menjunjung tinggi etika profesi. Terdapat lima nilai utama yang tercakup dalam integritas akademik yaitu kejujuran, kepercayaan, keadilan, menghormati dan tanggung jawab. Sebagai tenaga kesehatan seperti dokter diharapkan memiliki nilai-nilai integritas akademik dalam menjalankan profesinya nanti, sehingga hal ini harus dimulai dari dunia pendidikan ketika di universitas yaitu ketika menjadi mahasiswa program studi pendidikan dokter. Tujuan penelitian ini dilakukan untuk mengetahui apakah ada hubungan antara faktor personal (gender, sosio ekonomi, ras) dengan integritas akademik mahasiswa program studi pendidikan dokter. Metode: Desain penelitian adalah diskriptif analitik cross sectional yang melibatkan 77 mahasiswa program studi pendidikan dokter untuk menjadi responden. Kuesioner yang digunakan adalah kuesioner dari Roff (2009) yang telah dimodifikasi serta telah diuji validitas dan reliabilitas. Kuesioner bersisi 30 pernyataan tentang perilaku pelanggaran integritas akademik/kecurangan akademik serta setiap pernyataan diikuti oleh 5 pertanyaan yang menggambarkan persepsi dan perilaku mahasiswa. Analisis data dilakukan dengan menggunakan uji Chi-Square karena untuk mencari hubungan antara variabel berskala nominal dengan variabel berskala ordinal. Hasil: Hasil penelitian ini menunjukan bahwa hubungan antara gender dengan integritas akademik mahasiswa program studi pendidikan dokter didapatkan nilai p>0,05, kemudian hubungan antara sosio ekonomi dengan integritas akademik mahasiswa program studi pendidikan dokter didapatkan nilai p>0,05 dan hubungan antara ras dengan integritas akademik mahasiswa program studi pendidikan dokter didapatkan nilai p>0,05. Nilai p>0,05 memberikan hasil bahwa tidak terdapat hubungan diantara kedua variabel. Kesimpulan: Tidak ada hubungan antara faktor personal (gender, sosio ekonomi, ras) dengan integritas akademik mahasiswa program studi pendidikan dokter. Kata kunci: Faktor personal, gender, sisio ekonomi, ras, integritas Akademik, kecurangan akademik, pelanggaran integritas akademik, mahasiswa kedokteran.